A Method for Simulation Design of Refrigerated Warehouses using an Aspect-Oriented Modeling Approach - Cho, Gyu-Sung; Kim, Ho-Gyun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Refrigerated warehouses play a buffer function in a logistics system to meet the various demands of consumers. Over 50% of Korean refrigerated warehouses are located in Busan, and Busan has become a strategic region for cold chain industries. This paper suggests an aspect-oriented modeling approach for refrigerated warehouses to design and analyze in system design using simulation method considering the design conditions. The purpose of this paper is to formulate a new methodology for developing reusable, extendible, and modifiable control software for a refrigerated warehouse model using an aspect-oriented modeling approach.